Gambaran Self Efficacy Pada Keluarga Penderita Diabetes Melitus Dalam Menjalankan Upaya Pencegahan Diabetes Melitus - Nugraha Firdaus; Titis Kurniawan; sandra pebrianti (Universitas Mitra Indonesia, 2020)
Family with diabetes mellitus is a group that has the biggest risk to get diabetes mellitus. Nonetheless, a few families are found to do a prevention effort towards this issue. Self-efficacy is one of the factors that determines one’s behavior. This research purpose is to identify family with diabetes mellitus self-efficacy on carrying diabetes mellitus prevention effort.This research used quantitative descriptive with cross sectional method, involving 138 families with diabetes mellitus (siblings or descendant) who live on Tarogong public health center work area. The respondents were selected by using purposive sampling technique. The data was collected by using diabetes mellitus prevention self-efficacy questionnaire. The instrument was developed by the author based on related literature and had been tested for validity by two lecturers working in the field of diabetes mellitus. The collected data were analyzed as a description and displayed in percentage, frequency, mean. The general findings showed that the family’s self-efficacy for preventing diabetes mellitus was on high category (54,3%). Smoking and physical activity domain were found as the highest mean score, while exercise and health check-up were identified as the lower ones.The research result can be concluded that the family self-efficacy in preventing diabetes mellitus belongs to high category. Nevertheless, it is still important for community health center to develop a certain program that can involve family to improve low self-efficacy domain such as exercise and medical check-up. Keywords : Diabetes Mellitus, family, prevention, self-efficacy